Retrolabyrinthine approach for cochlear nerve preservation in neurofibromatosis type 2 and simultaneous cochlear implantation - Bento, Ricardo Ferreira; Monteiro, Tatiana Alves; Bittencourt, Aline Gomes; Goffi-Gomez, Maria Valeria Schmidt; de Brito, Rubens (International Archives of Otorhinolaryngology, 2013)
Introduction: Few cases of cochlear implantation (CI) in neurofibromatosis type 2 (NF2) patients had been reported in the literature. The approaches described were translabyrinthine, retrosigmoid or middle cranial fossa.Objectives: To describe a case of a NF2- deafened-patient who underwent to vestibular schwannoma resection via RLA with cochlear nerve preservation and CI through the round window, at the same surgical time.Resumed Report: A 36-year-old woman with severe bilateral hearing loss due to NF2 was submitted to vestibular schwannoma resection and simultaneous CI. Functional assessment of cochlear nerve was performed by electrical promontory stimulation. Complete tumor removal was accomplishment via RLA with anatomic and functional cochlear and facial nerve preservation. Cochlear electrode array was partially inserted via round window. Sound field hearing threshold improvement was achieved. Mean tonal threshold was 46.2 dB HL. The patient could only detect environmental sounds and human voice but cannot discriminate vowels, words nor do sentences at 2 years of follow-up.Conclusion: Cochlear implantation is a feasible auditory restoration option in NF2 when cochlear anatomic and functional nerve preservation is achieved. The RLA is adequate for this purpose and features as an option for hearing preservation in NF2 patients.
Keywords: Neurofibromatosis 2; Cochlear Implantation; Hearing Loss